2011
DOI: 10.1111/j.1365-2621.2011.02611.x
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide–taurine adducts formation as a key mechanism for taurine’s inhibitory effect on acrylamide formation

Abstract: Amino acids have attracted increasing attention in developing effective inhibitors on acrylamide (AA) formation during food processing. The main purpose of this study was to evaluate the inhibitory effect and mechanism of taurine (Tau) on AA formation. In the presence of Tau, AA formation was effectively inhibited in asparagine ⁄ glucose (Asn ⁄ Glc) model system. Results also showed that Glc content was decreased as Glc-Tau solution was heated, which indicated that Tau could react directly with Glc in the Mail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Besides, TA addition during food processing significantly inhibits acrylamide formation through directly reacting with AA to promote formation of AA-TA and AA dimmer-TA adducts [5]. Studies have reported that TA can prevent DNA damage at physiological concentrations with hepatoprotective effects through inhibition of extracellular matrix accumulation in experimental liver fibrosis and reverse of liver function tests in rats with hepatic failure.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, TA addition during food processing significantly inhibits acrylamide formation through directly reacting with AA to promote formation of AA-TA and AA dimmer-TA adducts [5]. Studies have reported that TA can prevent DNA damage at physiological concentrations with hepatoprotective effects through inhibition of extracellular matrix accumulation in experimental liver fibrosis and reverse of liver function tests in rats with hepatic failure.…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been designed to decrease AA during food processing, such as reducing the contents of precursors, optimising process parameters, using novel processing methods and adding some AA inhibitory agents . In particular, the AA content could be reduced significantly when free amino acids other than Asn or a protein‐rich food component were added to a Asn/Glc model system or food matrix . Since this operation would raise little concern regarding the artificial chemicals in foods and no changes to the sensory quality of food products, it is more practical for the food industry to add amino acids in order to inhibit the formation of acrylamide than through the use of other strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The key intermediates were analyzed using UPLC-QTOF-MS on a Waters Xevo G2-S UPLC/MS/MS platform equipped with a reversed-phase column (Acquity UPLC HSS T3, 100 × 2.1 mm, 1.7 μm) according to previous reports, with some modifications. 27,31 H 2 O (A) and 100% acetonitrile (B) were used as mobile phase and a linear gradient elution was used as follows: 1% B for 1 min, 1 to 60% B (1-4 min), 60-100% B (4-8 min), 100-1% B (8-11 min) and finally re-equilibration of the column with 99% A for 2 min at a flow rate of 0.3 mL min −1 and a column temperature of 45 °C. The individual intermediate was detected in ESI+ mode and the mass ranged from 50 to 1200 Da.…”
Section: Identification Of Key Intermediates In Model Systemsmentioning
confidence: 99%